Comunicações Transacionais para Melhorar o Relacionamento com o Cliente - Ferreira, José Bernardo Sousa Maia Rocha (2022)
Transactional communications are messages that are sent as soon as an action is completed by a user typically using a Web application. Therefore, it consists of a relationship strategy whose objective is to strengthen the ties between the organization and its customers, as well as provide relevant information. Usually, transactional communications work automatically, and messages can be scheduled to be sent whenever an action is completed. However, small and medium organizations may not have the necessary funds and means to create and maintain a Web application or to integrate it with a transactional communication channel. In this dissertation, a transactional communication tool called QuickMessage is analyzed and improved, which sends Short Message Service (SMS) transactional messages in a nonautomated way, with users having to manually trigger their sending at an exact moment. Since the QuickMessage tool only had one SMS channel, it was intended to implement other transactional channels, such as the Email channel, and also allow the scheduling of SMS messages and Emails. Evaluation methods based on software tests, usability questionnaires, and the Quantitative Evaluation Framework (QEF) are used to evaluate the final solution.